Inactivation of Uropathogenic Escherichia coli in Ground Chicken Meat Using High Pressure Processing and Gamma Radiation, and in Purge and Chicken Meat Surfaces by Ultraviolet Light - Sommers, Christopher H.; Scullen, O. J.; Sheen, Shiowshuh (Frontiers in Microbiology, 2016)
Extraintestinal pathogenic Escherichia coli (ExPEC), including uropathogenic E. coli (UPEC) are common contaminants in poultry meat and may cause urinary tract infections after colonization of the gastrointestinal tract and transfer of contaminated feces to the urethra. Three nonthermal processing technologies used to improve the safety and shelf-life of both human and pet foods include high pressure processing (HPP), ionizing (gamma) radiation (GR), and ultraviolet light (UV-C). Multi-isolate cocktails of UPEC were inoculated into ground chicken which was then treated with HPP (4 oC, 0-25 min) at 300, 400 or 500 MPa. HPP D10, the processing conditions needed to inactivate 1 log of UPEC, was 30.6, 8.37, and 4.43 min at 300, 400, and 500 MPa, respectively. When the UPEC was inoculated into ground chicken and gamma irradiated (4 and -20 oC) the GR D10 were 0.28 and 0.36 kGy, respectively. The UV-C D10 of UPEC in chicken suspended in exudate and placed on stainless steel and plastic food contact surfaces ranged from 11.4 to 12.9 mJ/cm2. UV-C inactivated ca. 0.6 log of UPEC on chicken breast meat. These results indicate that existing nonthermal processing technologies such as HPP, GR, and UV-C can significantly reduce UPEC levels in poultry meat or exudate and provide safer poultry products for at-risk consumers.